Adapting in the Arctic: Habitual activity and landscape interaction in Late Holocene hunter‐gatherers from Alaska. Issue 1 (29th March 2021) - Temple, Daniel H.; Rosa, Emily R.; Hunt, David R.; Ruff, Christopher B.
Abstract: Objectives: This study compares lower limb diaphyseal robusticity between Native Alaskan hunter‐gatherers to reconstruct patterns of mobility and engagement with terrain. Materials and methods: Ancestral remains included in this study date between 600 and 1800 C.E. and were divided into three regions: Coastal Bay, Far North Coastal, and Inland/Riverine. Cross‐sectional properties were determined at femoral and tibial midshafts and standardized by powers of body mass and bone length. Results: Consistently elaevated areas and second moments of area were found in ancestral remains from the Far North Coastal, while the Coastal Bay remains had reduced diaphyseal robusticity. Individuals from the Inland/Riverine region were intermediate in robusticity for male femora, but similar to the Coastal Bay group for females. Sexual dimorphism was greatest in the Inland/Riverine ancestral remains and comparable between Coastal Bay and Far North Coastal regions. Conclusions: Ancestral remains from the Far North Coastal region have the greatest diaphyseal robusticity in response to intensive hunting and travel over rugged terrain. Reduced sexual dimorphism in the Far North Coastal region suggest female participation in hunting activities. Intermediate diaphyseal robusticity among Inland/Riverine males and increased sexual dimorphism reflects diverse patterns of mobility in relation to the hunting cycle between males and females. Reduced diaphyseal robusticity and sexual dimorphism among the Coastal Bay group is associated with sedentary villages established around net fishing in regions with low relief. Such findings argue against technocentric views of sedentism in hunter‐gatherer lifeways and generally reflect diverse adaptive strategies and interaction with local terrain among Indigenous Late Holocene hunter‐gatherers of Alaska. Abstract :